Role of Human Capital in Market Orientation – Innovation Relationship - Siddique, Adnan; Nazir, Adnan; Adnan, Sabahat; Duryab, Muhammad Aamir (Journal of Management and Research, 2021)
Academics and practitioners have considered and regarded innovation as a source to gain sustainable competitive advantage (SCA) over rival firms. Although market orientation (MO) and innovation have been studied and found to impact a firm’s ability to innovate separately, how they interact with each other has not been studied before. Drawing from the theory of organizational learning, this study proposes that human capital (HC) mediates the relationship between MO and innovation. The proposed relationship was empirically tested using data collected from managers of the textile sector of Pakistan. The results reveal that human capital and market orientation separately affect innovation while HC partially mediates MO and innovation relationship. Practical and future research implications of the study have also been discussed.